2017
DOI: 10.3390/toxins9070196
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol Biomarkers in the Urine of UK Vegetarians

Abstract: Deoxynivalenol (DON) is produced by Fusarium graminearum and is one of the most commonly occurring trichothecenes. Vegetarians are alleged to be a high-risk group for DON exposure due to high intakes of cereals susceptible to the growth of the mycotoxin. This study provides the levels of DON and de-epoxi Deoxynivalenol (DOM-1) in urine analysed by liquid chromatography-mass spectrometry (LC-MS) in UK vegetarians. Over two consecutive days, morning urine samples were collected from 32 vegetarians and 31 UK adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…The percentages exceeding the PMTDI for DON in children and adolescents are much higher than previous estimations reported in UK adults. Wells et al (2017) [ 18 ] analysed urine samples of 31 adults in the UK and <3% exceeded the PMTDI. In an earlier study conducted by Turner et al in the UK, 17% of the participants exceeded the PMTDI (0.008–1.24 μg/kg·b.w./day), although the number of urine samples analysed was small ( n = 6) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentages exceeding the PMTDI for DON in children and adolescents are much higher than previous estimations reported in UK adults. Wells et al (2017) [ 18 ] analysed urine samples of 31 adults in the UK and <3% exceeded the PMTDI. In an earlier study conducted by Turner et al in the UK, 17% of the participants exceeded the PMTDI (0.008–1.24 μg/kg·b.w./day), although the number of urine samples analysed was small ( n = 6) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies which assessed urinary DON levels and its metabolites in adult populations showed exposure levels close to, or even higher than, the PMTDI [ 12 , 15 , 18 ]. There is also interest in investigating DON exposure in potentially susceptible population groups due to their physiological status (e.g., pregnancy) [ 19 ]; dietary habits (e.g., vegetarians) [ 18 ]; and age (i.e., children and adolescents) [ 20 , 21 , 22 ]. Children are considered to be at risk for greater relative DON exposure than adults due to their higher food and fluid intake per kg of body weight compared to adults, child/adult metabolic differences, limited ability for detoxification, and on-going bodily system development including the immune and central nervous system [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary DON biomarkers have been shown to be a good indicator for DON exposure as they show a good correlation with food consumption especially with cereal, maize and wheat products [8][9][10][11][12][13][14][15] . According to the dietary recall survey, the major source for DON exposure for the Japanese university students tested here was likely to be wheat products.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme hydrolysis during the extraction step has been proposed in order to increase the accuracy in determining DON levels in urine, which converts the conjugated DON back to its free form so that total urinary DON is measured to assess the exposure 7) . Total DON (extraction with enzyme digestion), free DON, DON-3-GlcA and DON-15-GlcA are all suitable biomarkers for DON exposure assessment, while DOM-1 showed a very low concentration in human urine samples [8][9][10][11][12][13][14][15] . The benefit of utilizing biomarker measurement, compared to the traditional dietary exposure assessment, to assess the DON exposure is that this method can cover DON exposure through different exposure routes.…”
Section: Introductionmentioning
confidence: 99%
“…Acute exposure can cause diarrhea, vomiting, leukocytosis, hemorrhage, and, with extremely high exposure, even death (Knutsen et al, 2017). This is the reason why a few years ago, researchers raised questions about the safety of DON when exposed to high-risk groups, including children and vegetarians (Wells et al, 2017).…”
Section: Deoxynivalenolmentioning
confidence: 99%